1974
DOI: 10.1021/jo00929a026
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of dispiro-1,3-cyclobutanediones in methylene chloride and methanol solutions

Abstract: The photolysis of dione 3 ( = 4) in methylene chloride leads mainly to the isomeric, photolabile enol lactone 6. Diones 3 ( = 5, 6, or 7) on irradiation in methylene chloride solutions lead to 20, 50, and 40% yields of 4 (re = 5, 6, or 7), respectively. Pentamethyleneketene and hexamethyleneketene were also formed from diones 3 (re = 6 or 7). Little cycloelimination occurs in the case of dione 3 (re = 5). Small amounts of cycloalkanones are also formed from diones 3 (re = 5, 6, or 7) (less than 10%). Dione 3 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

1974
1974
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
2
4
0
Order By: Relevance
“…[52] Compounds 1a and 1b have relatively low quantum yields between 0.03-0.04. In agreement with previous reports, the cyclohexyl diones 1c, [46,47] and 1d, undergo efficient photoreaction, with quantum yield of decarbonylations of 0.34 and 0.33, respectively (Table 1).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…[52] Compounds 1a and 1b have relatively low quantum yields between 0.03-0.04. In agreement with previous reports, the cyclohexyl diones 1c, [46,47] and 1d, undergo efficient photoreaction, with quantum yield of decarbonylations of 0.34 and 0.33, respectively (Table 1).…”
Section: Resultssupporting
confidence: 92%
“…[49] Previous work by Krapcho reported that photolysis of cyclobutanediones 1a-1c in dichloromethane undergo either a formal reverse [2+2] cycloaddition to generate the ketenes 2a-c, or two sequential decarbonylations to form alkenes 4a-4c via the corresponding cyclopropanones 3a-3c. [47] In agreement with Krapcho's previous studies, diones 1a-c undergo efficient photoreaction upon irradiation at 312nm in dichloromethane (DCM). The photochemical reactions were monitored by gas chromatography.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Other examples of reaction-enabling substituents that support the generality of the solid-state reaction include the a,a-dialkoxy groups of bisketal 181, which has an aromatic p-system out of alignment to stabilize the radical intermediates (Scheme 2.44) [76]. The spiro-cyclobutanone 183 [77] and diphenyl cyclopropenone 185 [78] serve to illustrate an alternative strategy to enable the solid-state reaction based on the release of strain energy. Compound 183 reacts by a double decarbonylation process to give bis-cyclohexylidene 184, and cyclopropenone 185 reacts with an unprecedented quantum chain transformation to generate diphenylacetylene 186.…”
Section: Reactivity and Stabilitymentioning
confidence: 99%
“…6), except that 25a exclusively rearranged to the thermally and photochemically sensitive enol 13-lactone 29a. 40 Irradiation of 25 in methanol in Pyrex vessels afforded a rather complex spectrum of products ( Fig. 11).…”
mentioning
confidence: 99%